ROTOR SYSTEM OF MAGNETIC SUSPENDING FLYWHEEL OF DYNAMIC RESEARCH BASED ON FINITE ELEMENT ANALYSIS - SONG JunChen; OUYANG HuiMin; ZHANG GuangMing (Jixie qiangdu)
The 3D model of the magnetic bearing-rotor was made by using solidworks and seamless link from solidworks to ansys workbench was realized. The gyroscopic effect of the rotor was considered. Also the nature frequency,the modal map and the campbell diagram of rotor system was got through the analysis. In addition,we consider the effect of unbalance force on the rotor. According to the Different locations,we conduct the unbalance harmonic response analysis,successfully verify the result of modal analysis. The verification show that the nature frequency of rotor system is reasonable,which can provide information about the vibration of system and the optimization of the dynamic characteristics.